Occurrence of Talavera aperta (Miller, 1971) (Araneae: Salticidae) in Poland - Rozwałka, Robert; Rutkowski, Tomasz; Sienkiewicz, Paweł; Renn, Katarzyna (Biological Letters, 2016)
Talavera aperta is a rare member of the Salticidae (jumping spiders). Its presence in Poland has been questioned. This paper presents data on 20 new localities of this poorly known species and a map of its distribution in western and central Poland. Detailed drawings of the male body, male palps and the female epigynum are also provided. T. aperta was usually collected from dry, sunny habitats, mostly in June, although some specimens were recorded in other months. In winter, spiders of this species were found in shells of small snails (Cepaea spp., Helicella obvia).